Thoracoscopic primary repair of esophageal atresia and tracheoesophageal fistula: Our early experience - Eslam Adel Ali; Khaled M. El Asmar; Tarek A. Hassan; Mohamed Moussa Dahab; Mostafa M. Elghandour (EL-Med-Pub, 2024)
Background: Thoracoscopic repair of esophageal atresia (EA) and tracheoesophageal fistula (TEF) has been practiced more frequently in the past two decades. This study focuses on assessing our early experience with implementing this minimally invasive technique in neonates. Methods: Neonates with EA/TEF who were admitted to the NICU at Ain Shams University hospitals during the period from 2021 to 2022 were enrolled in the study. Thoracoscopic primary repair was performed for neonates with a body weight exceeding 2 kg. Neonates with associated major cardiac, pulmonary, and neurological anomalies and long gap atresia were excluded from the study. Results: A total of 38 neonates presented with EA/TEF during the study period. Out of these neonates, 12 cases underwent thoracoscopic primary repair. The thoracoscopic approach was used to complete all necessary repairs, and no intraoperative complications occurred. The mean operating time was 125 minutes, ranging from 105 to 150 minutes. No evidence of leakage was found in any case, as determined by both clinical and radiological contrast swallow examinations. The mean ventilation time was 7.2 days, and the mean hospital stay was 21 days. There were four deaths attributed to complications related to barotrauma and sepsis. Conclusion: Thoracoscopic repair of EA can be performed safely, which yields favorable functional and cosmetic outcomes. However, it remains a challenging procedure that requires a long learning curve.